Residentification of Antibiotic Resistant Bacteria Isolated From the Handphones of Male and Female Users in Nilai - Ramandey, Erlies Patricia (2018)
Although handphones have many functions, the overuse of handphones can lead to transmission of bacteria including antibiotic resistant bacteria. Previous study had successfully isolated bacteria from handphones, some of the isolates were poorly identified. In addition, the susceptibility pattern of the isolate were not convincing. Thus, the objectives of this study were to re-isolate and re-identify the bacterial isolates obtained by previous study as well as to reconfirm the resistance patterns of the bacterial isolates and to compare the distribution of the antibiotic resistant bacteria between the handphones of male and female users in Nilai. The pure cultures of isolates were obtained using the dilution streak technique and subjected to gram staining and biochemical assays before proceeding to antibiotic susceptibility test using vancomycin, rifampicin, ciprofloxacin, gentamycin, ampicillin, cefoxitin, streptomycin, ceftriaxone, and ofloxacin. The isolates were confirmed using Bergey’s Manual of Determinative Bacteriology. The antibiotic resistant pattern were determined using the Clinical and Laboratory Standard Institute, 2017. Few possible genus and species were isolated, which were Staphylococcus aureus, Staphylococcus epidermidis, Bacillus subtilis, Propionibacterium sp, Neisseria sp, Enterobacter sp, and Stomatococcus sp. Fifty-six isolates were obtained in which, 48 isolates were gram positive while 8 were gram negative. 30 (53%) isolates showed resistance towards at least one antibiotic. However, 11 (20%) isolates were susceptible to all the tested antibiotics. However, the susceptibility of 15 (27%) isolates could not be defined because the genera of the isolates could not be identified. The data obtained from the antibiotic susceptibility tests were analysed statistically using the chi-square and indicated that there were no significant differences on the number of antibiotic resistant bacteria isolated from handphones of male and female users.